Penerapan Mobile Health Application Terintegrasi pada Rekam Medis Elektronik dalam Melakukan Monitoring Luka Tekan - Puti Rahmitha Sany; Tuti Herawati; Liya Arista (Journal of Telenursing (JOTING), 2023)
This study aimed to determine the effectiveness of the integrated mobile health application in electronic medical records in monitoring pressure sores. The research method used is a literature review with research journal sources from 2018-2022 on the Scopus database, Sage Publishing, ProQuest, Science Direct, ClinicalKey for Nursing, and PubMed with the keywords electronic health record, mobile health, and pressure injury. The results showed that a review of 10 research journals found that mobile health applications integrated into electronic medical records could assist nurses in monitoring pressure sores. In conclusion, a mobile health application integrated into electronic medical records is considered effective in monitoring pressure sores. Keywords: Electronic Health Record, Mobile Health, Pressure Injury